Taxon matters: promoting integrative studies of social behavior. Issue 4 (April 2015) - Taborsky, Michael; Hofmann, Hans A.; Beery, Annaliese K.; Blumstein, Daniel T.; Hayes, Loren D.; Lacey, Eileen A.; Martins, Emília P.; Phelps, Steven M.; Solomon, Nancy G.; Rubenstein, Dustin R.
Highlights The complexity of social behavior requires integrated studies across analysis levels. Data should include multiple physiological, environmental, and social conditions. Model systems used in neural and ecological studies traditionally diverge. Recent conceptual and technical advances allow the taxonomic divide to be overcome. Synthesis of behavioral research requires the development of predictive, testable models.